Unraveling the connections: Learning styles, critical thinking skills and mathematics performance among industrial technology students - Maquiling, Everlou E.; Desabella, Romeo V. (Edelweiss Applied Science and Technology, 2025)
This study examines the relationships between learning styles, critical thinking skills (CTS), and mathematics performance among Industrial Technology students using a descriptive-quantitative approach. The researchers utilized mean, standard deviation, Spearman rank order coefficient correlation, and regression analysis as statistical treatments. Findings show significant correlations between CTS and math performance, with visual and kinesthetic learning styles positively influencing outcomes. The study underscores the importance of fostering analytical reasoning and adaptive teaching methods aided by a self-learning module developed in technical education. Predicting the students’ academic performance can be computed through this model: y = 1.051 X1 – 0.762 X2 – 1.055 X3 + 0.964 X4 + 0.495 X5 – 0.406 X6 + 0.374 X7 + 0.700 X8 – 0.806 X9 + 0.655 X10 + 76.965. The regression model provides valuable insights into the relationship between learning styles, CTS, and academic performance, explaining 19.1% of the variance in the dependent variable. While the explanatory power is modest, the findings highlight key predictors significantly impacting learning outcomes. These results highlight the need for teaching strategies that foster critical thinking and align with diverse learning styles. Future research should include factors such as teachers’ motivation and instructional methods to enhance predictive accuracy and intervention design.